Microbial Diversity in the Glacial Ecosystem of Antarctic, Arctic, and Tibetan Plateau: Properties and Response to the Environmental Condition - Sharma, Birendra Prasad; Adhikari, Subash; Paudel, Ganesh; Adhikari, Namita Paudel (Janapriya Journal of Interdisciplinary Studies, 2020)
Microorganisms, as successive members of the food web, play a major role in biological processes. They are found in environments ranging from extremely hot to harsh cold temperatures. Thus, the study of bacterial communities in various ecosystems is of great concern around the world. The glacier is one of the parts of the cryosphere, which is the key component and sensitive indicator of climatic and environmental changes. A glacial ecosystem is a habitat for various microorganisms, i.e., autotrophic and heterotrophic. Different physicochemical parameters like temperature, pH, electrical conductivity, the input of nutrient concentration, precipitation, ions concentrations, etc. influence the microbial diversity in the glacial ecosystem for their metabolic processes. Successive studies of bacterial communities in the Himalayan glacial ecosystem are reliable proxies to know the relationships between microbial biodiversity and climate change since the Himalayan glaciers are free from anthropogenic activities. After the study of the relevant literature, it is clear that the researches. have been carried out in the Polar Regions, and the Tibetan plateau mainly focused on the glacial ecosystem. This review concluded that Proteobacteria, Bacteroidetes, Cyanobacteria, Firmicutes, Verrucomicrobia, and Actinobacteria were the most dominant bacterial phyla via 16S rRNA clone libraries and Illumina MiSeq. Alter in landscapes, nutrient cycles, exposure of light, shifting on the concentration of different elements, glacier retreats were the major components for survival strength of dominant bacterial phyla. However, limited studies on the glacial ecosystem of the Himalayas have been published. Thus, the study of bacterial abundance, diversity, and community in the Himalayas will help plug this research gap.